2017
DOI: 10.1016/j.jcat.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and branching on the nature and stability of alkene cracking intermediates in H-ZSM-5

Abstract: Catalytic cracking of alkenes takes place at elevated temperatures in the order of 773–833 K. In this work, the nature of the reactive intermediates at typical reaction conditions is studied in H-ZSM-5 using a complementary set of modeling tools. Ab initio static and molecular dynamics simulations are performed on different C4single bond C5 alkene cracking intermediates to identify the reactive species in terms of temperature. At 323 K, the prevalent intermediates are linear alkoxides, alkene π-complexes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
175
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(189 citation statements)
references
References 123 publications
11
175
3
Order By: Relevance
“…Sauer and co‐workers reported that tert ‐butyl cation was more favorable than isobutene and surface alkoxides in H‐FER zeolite . However, with respect to linear alkenes such as pentene, it was found that linear alkoxides and alkene π‐complexes were prevalent intermediates in H‐ZSM‐5 at 323 K, and an increase in the temperature to 573 K, which is near to practically operational methanol‐to‐hydrocarbons temperature, caused alkoxides to be metastable as a result of enormous entropic loss, while π‐complexes were still highly stable . This shows that the exact state (π‐complex, carbenium ion or alkoxide) of alkene adsorbing on Brønsted acidic zeolites depends on the zeolite framework, isomers structure and reaction temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Sauer and co‐workers reported that tert ‐butyl cation was more favorable than isobutene and surface alkoxides in H‐FER zeolite . However, with respect to linear alkenes such as pentene, it was found that linear alkoxides and alkene π‐complexes were prevalent intermediates in H‐ZSM‐5 at 323 K, and an increase in the temperature to 573 K, which is near to practically operational methanol‐to‐hydrocarbons temperature, caused alkoxides to be metastable as a result of enormous entropic loss, while π‐complexes were still highly stable . This shows that the exact state (π‐complex, carbenium ion or alkoxide) of alkene adsorbing on Brønsted acidic zeolites depends on the zeolite framework, isomers structure and reaction temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The static periodic DFT calculations are performed using the Vienna Ab Initio Simulation Package (VASP 5.3) using a methodology frequently applied in literature . We here opted to use the revPBE functional due to its improved performance for solid‐state calculations compared to the commonly used PBE functional .…”
Section: Computational Methodologymentioning
confidence: 99%
“…As earlier work showed that a partial Hessian vibrational analysis (PHVA) is able to predict adsorption entropies within a 10–15 J/(mol K) error of computationally more demanding full Hessian calculations (FHVA) and experimental data, it has become a frequently applied and attractive methodology . For this reason, it is also used for the normal mode analysis (NMA) in this work using TAMkin .…”
Section: Computational Methodologymentioning
confidence: 99%
“…Ethylene aromatization easily occurs on the BAS of a zeolite. Four different possibilities for alkene activation are mentioned in the literature (Figure ) . But most papers assume that ethylene is activated by forming a carbocation (C 2 H 5 + ) with the help of the proton from the acid site .…”
Section: Ethylene Aromatizationmentioning
confidence: 99%
“… Four different modes of activation for an alkene – 1: Van der Waals complex, 2: π ‐complex, 3: carbenium ion, 4: alkoxide …”
Section: Ethylene Aromatizationmentioning
confidence: 99%